Procedura kontraktowania świadczeń przez Narodowy Fundusz Zdrowia. Próba analizy SWOT - Iłowiecka, Katarzyna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
Contracting of health care benefits is a very important tool that allows a payer to create desired structure, considering the needs notified by the patients, the cost-effectiveness and the quality of the benefits. Contracting is aimed at attaining a number of important tasks such as the implementation of the existing rules of access to health care and the development of supply and demand in a way that facilitates the implementation of the adopted health policy. Contracting of health care benefits is thus an important tool enabling to introduce the regulated market and regulated competition. Therefore, a correct model for contracting of benefits is essential for correct exchanges of the limited (and specific) resources on the healthcare market. The purpose of this article is to assess the contracting of health care benefits by the National Health Fund. The following areas impacting on contracting of benefits were analysed: sources of financing, benefits purchase planning, valuation of benefits and the procedures for the award of contracts. A SWOT analysis was used to perform the analysis. At present the contracting of health care benefits in Poland is regulated by the Act of 27 August 2004 on health care benefits financed from public funds (consolidated text: Journal of Laws 2015, item 581, as amended). The article describes the legal situation on 31 March 2016. The conclusions from the analysis confirm the need for change, in particular by improving the cost efficiency and the implementation of activities promoting comprehensive care of a patient.